ANALYSIS OF LIQUEFACTION POTENT ANALYSIS OF LIQUEFACTION POTENTIAL USING THE ANALYTICAL HIERARCHY PROCESS METHOD IN BANTUL DISTRICT, YOGYAKARTA PROVINCE, INDONESIA: ANALYSIS OF LIQUEFACTION POTENTIAL - Nurhaci, Dian Susri (Institut Teknologi Nasional Yogyakarta, 2024)
Abstract — The earthquake that struck the Bantul district of Yogyakarta on May 27, 2006, with a Richter scale value of 6.3, caused sandboils in various areas in Bantul Regency. These symptoms are referred to as liquefaction events, and the phenomenon is fascinating to research. These symptoms are referred to as liquefaction events, and the phenomenon is intriguing to researchers. Liquefaction in Bantul Regency is induced by the area's Young Volcanic Deposits of Merapi Volcano and shallow groundwater table, which can result in saturated soil during an earthquake. The research was conducted to assess the potential hazards of liquefaction. The data used in this research includes geological maps, groundwater depth maps, fault distance maps, river distance maps, and slope maps. The method used is the Analytical Hierarchy Process (AHP) to determine the weight of each parameter utilized, employing Geographic Information System software to overlay maps based on the obtained weight values, allowing the liquefaction threat potential map to be classified into high, medium, and low threats. According to the findings of this study, the lowland area between the Bedog and Opak rivers has a high liquefaction potential due to the presence of Young Volcanic Deposits of Merapi Volcano going back to the Quaternary epoch and a relatively shallow groundwater table. In contrast, the hilly terrain west of the Bedog River and east of the Opak River has a low liquefaction potential due to Tertiary sedimentary rocks and a deeper groundwater table